The Relationship between Middle Manager Innovative Self-Efficacy and Innovation: The Case of the UAE Government Entities - BIN-MANA, ALFADHEL (2021)
Middle managers continue to be essential for organizations around the world. These are managers who are tasked with overseeing the day-to-day activities of organizations. Additionally, these are also the managers who contribute towards the innovation of organizations. This takes place because of their innovative self-efficacy. Therefore, middle managers have proven instrumental in helping organizations not to overlook innovation which has been a long running problem for many of them. the situation is even more so dire for government-based organizations in the UAE. For this reason, it remains instrumental to gain insight into the contribution of middle managers towards fostering innovation in public organizations. This study examined the impact of the innovative self-efficacy of middle managers on their innovative work behavior. Middle managers continue to be overlooked in the organizational environment and this significantly hampers their contribution to innovations in their respective companies. Hence, it was important, through this research, to examine the innovative self-efficacy of middle managers and how it influences their innovative work behavior. To measure innovative self-efficacy, three key constructs including self-efficacy towards guiding groups, self-efficacy towards influencing employees, and self-efficacy towards using innovations were taken into consideration. Innovative work behavior was measured using idea generation, idea promotion, and idea realization. Previous studies have highlighted the plight of middle managers in the organizational environment and the challenges that they continue to face in terms of role recognition. Despite the invaluable services they deliver to their organizations through identification of new opportunities, overseeing daily operations of the organization, and implementation of change, their roles continue to be overlooked. To understand how the innovative self-efficacy of middle managers influences their innovative work behavior, this research utilized the quantitative research design. Questionnaires were used to collect data from 151 middle managers in different government departments in the UAE. Ordinal least squares (OLS) were applied to the regression analysis. The findings revealed that there is a relationship between middle managers’ innovative self-efficacy and their innovative work behavior. Second, self-efficacy towards guiding groups is related to the innovative work behavior of middle managers. Third, it was established that self-efficacy towards influencing employees is positively related to innovative work behavior. Further, the findings revealed that self-efficacy towards using innovations is positively related to innovative work behavior of middle managers. It was also noted that there is no significant difference in the mean innovative behavior between male and female middle managers. The results support all the developed hypotheses. Most importantly, with a greater level of self-efficacy, middle managers become more innovative. This study contributes to the understanding of the significant role that middle managers play in the organization. Notably, this study provides a platform that would enable organizations to understand who middle managers are, their roles, and their contribution to innovations if given a chance to work without overlooking their roles. Overall, based on the findings of this study, middle managers will be more appreciated in the organizational context in the UAE government departments. Keywords: Middle managers, innovative self-efficacy, innovative work behavior, role.